Mental health policy in Eastern Europe: a comparative analysis of seven mental health systems - Dlouhy, Martin (BMC health services research, 2014)
BACKGROUND: The objective of this international comparative study is to describe and compare the mental health policies in seven countries of Eastern Europe that share their common communist history: Bulgaria, the Czech Republic, Hungary, Moldova, Poland, Romania, and Slovakia. METHODS: The health policy questionnaire was developed and the country-specific information was gathered by local experts. The questionnaire includes both qualitative and quantitative information on various aspects of mental health policy: (1) basic country information (demography, health, and economic indicators), (2) health care financing, (3) mental health services (capacities and utilisation, ownership), (4) health service purchasing (purchasing organisations, contracting, reimbursement of services), and (5) mental health policy (policy documents, legislation, civic society). RESULTS: The social and economic transition in the 1990s initiated the process of new mental health policy formulation, adoption of mental health legislation stressing human rights of patients, and a strong call for a pragmatic balance of community and hospital services. In contrast to the development in the Western Europe, the civic society was suppressed and NGOs and similar organizations were practically non-existent or under governmental control. Mental health services are financed from the public health insurance as any other health services. There is no separate budget for mental health. We can observe that the know-how about modern mental health care and about direction of needed reforms is available in documents, policies and programmes. However, this does not mean real implementation. CONCLUSIONS: The burden of totalitarian history still influences many areas of social and economic life, which also has to be taken into account in mental health policy. We may observe that after twenty years of health reforms and reforms of health reforms, the transition of the mental health systems still continues. In spite of many reform efforts in the past, a balance of community and hospital mental health services has not been achieved in this part of the world yet.
Keywords: Surveys and Questionnaires; Health Policy; Universal Health Insurance; Humans; zdravotní politika; duševní zdraví; Polsko; lidé; Hungary; Poland; všeobecné zdravotní pojištění; Rumunsko; Slovakia; Slovenská republika; průzkumy a dotazníky; Maďarsko; Bulgaria; Romania; Moldavsko; Czech Republic; Mental Health Services; služby péče o duševní zdraví; Bulharsko; Česká republika; Moldova; Mental Health